50 - FALL RISK FACTOR FOR FRACTURES OF THE FEMUR IN ELDERLY (Fiep Bulletin - online, 2011)
Aging is a stage of life where human beings are more vulnerable to functional disorders, morphological and biochemical changes reflecting a reduced homeostatic capacity. It results in constantly changes in organism; in this way elderly people are more prone to develop harmful events to health disease process that may worsen and lead to death as fall followed by fracture, mainly femur. Factors that may contribute to occurrence of fall are: advanced age, female gender, history of falls, immobility, muscle weakness and abnormal walk as facilitators of the fall. It is aimed to study elderly patients victimized of falls from a Trauma-Orthopedics Hospital in Natal/RN. It is an exploratory and descriptive study with qualitative approach carried out at Trauma-Orthopedics Hospital in Natal/RN. Regarding to the results 24 (80%) elderly were female, white race was 15 (50%) and 29 (96,7%) of the population stated not be directed dependent on someone to care of them before the fall. It is conclude that greater degree of independence in activities of daily life of elderly, greater is the possibility of falling and fracturing of the femur
Keywords: Elderly; Fall Accidents; External Causes; Fractures of the Femur